La pena: función y presupuestos - Meini Mendez, Iván (2013)
Legitimacy of criminal sanction is originated on its own purposes pursued in a state governed by the Rule of Law. That legitimacy should include the penalty as well as security measures, bearing in mind that both are imposed to someone breaking a rule of conduct, and therefore, someone capable to do it. Reviewing penal capacity or criminal liability concepts is required because if penal capacity means the capacity to understand the reality and adjust the behavior to it, and if every legitimate criminal sanction have to be imposed to someone who have the capacity of break it, then security measures also have to be imposed only to people responsible, capable to understand rules and act in accordance. With regard to people not subject to criminal liability they are standing outside Criminal Law and punish them would be illegitimate. In this line, criminal liability should be seen not only as a crime assumption but also as a basic statement for any dialogue the state shall have with the citizens: at the level of crime itself, proceedings and sentence execution .